The longitudinal association between objectively-measured school-day physical activity and academic achievement in US elementary school students - Paul N. Elish; Cassandra S. Bryan; Peter J. Boedeker; Hannah G. Calvert; Christi M. Kay; Adria M. Meyer; Julie A. Gazmararian (BMC, 2022)
Abstract Background It is recommended that school-aged children accrue 30 minutes of daily moderate-to-vigorous physical activity (MVPA) in school. Current literature is inconclusive about the long-term associations between school-based physical activity and academic achievement. In this study, we use a large sample and longitudinal design to rigorously evaluate whether school-day MVPA is associated with academic achievement. Methods In a diverse suburban public school district, 4936 Grade 4 students were recruited in 40 elementary schools. Students wore accelerometers to measure school-day MVPA for 15 days across three semesters. Academic performance data was collected across Grade 3 fall to Grade 5 spring, including teacher-assigned grades and standardized test scores. Multilevel modeling was conducted controlling for student demographics and school characteristics. Results Cross-sectional analyses found small negative associations in Grade 4. Grade 4 full-year mean daily school-day MVPA had β = −-0.066, β = −-0.063, β = −-0.066, and β = −-0.058 associations (p <  0.001) with Grade 4 math, reading, spelling, and writing grades respectively, and Grade 4 full-year mean daily school-day MVPA had β = −-0.206 and β = −-0.283 (p <  0.001) associations with Grade 4 math and English Language Arts (ELA) standardized test scores respectively out of approximately 500 points. Longitudinal analyses found no significant associations between Grade 4 full-year mean daily school-day MVPA and Grade 5 Fall course grades. Results also indicated small negative associations for students attaining 30+ minutes of daily school-day MVPA compared to those attaining less than 15 minutes, but only in Grade 4 Fall cross-sectional analyses where teacher-assigned reading, spelling, and writing grades were − 1.666, − 1.638, and − 1.993 points lower respectively (p <  0.001). Conclusion The cross-sectional findings, while statistically significant in a negative direction, have a negligible association when translated practically. For example, even if students attained twice the recommended amount of school-day MVPA - which would constitute an approximately 300% increase from current levels - results suggest that grades would only decrease by 2 points on a 100-point scale. Furthermore, longitudinal analyses suggest school-day MVPA does not have a predictive association with course grades or standardized test scores. Findings suggest school-based MVPA implemented in accordance with recommendations does not meaningfully detract from academic progress. Trial registration ClinicalTrials.gov , NCT03765047. Registered 05 December 2018 - Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT03765047